Peran Mahasiswa Kuliah Kerja Nyata (KKN) dalam Meningkatkan Kualitas Kesadaran Kebersihan Lingkungan atas Pengelolaan Sampah Terhadap Masyarakat Sebagai Wujud Pengabdian di Desa Cijambe, Kecamatan Paseh, Kabupaten Sumedang: Pengabdian - Ghina Fauziyah Imansyah; Abid Naufal Habibburokhman; Fajar Abidin; Ferta Adriagil Putra Firdaus; Indah Lestari; Kartika Nuri Sakinatul Alim; Luthfi Ahmad Tamimi; Mela Ratna Sari; Rd Ghina Fithriyah; Rahma Arinda Putri Bhirawanto; Ramaditya Rahardian (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Community Service Program (KKN) of Universitas Muhammadiyah Bandung in Cijambe Village, Paseh District, Sumedang Regency, was implemented as a community engagement initiative to address the lack of awareness in household waste management. The program included a seminar entitled “Towards a Clean Cijambe Village: Strategies for Sustainable Waste Management”, direct assistance to local residents at the neighborhood level on organic and inorganic waste separation, as well as innovative eco-friendly product development such as compost, eco-enzyme, ecobrick, and multifunctional organic soap. The outcomes demonstrated an improvement in community knowledge and active participation in applying the 3R paradigm (Reduce, Reuse, Recycle), along with the adoption of new sustainable waste management practices. Beyond enhancing environmental cleanliness, the program also contributed to the creation of local economic opportunities through waste utilization. Thus, the role of KKN students is proven to be strategic in fostering environmental awareness, strengthening community capacity, and encouraging the establishment of a sustainable community-based waste management system.